ANALISIS PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP KESULITAN KEUANGAN PADA PERUSAHAAN SEKTOR INDUSTRI MANUFAKTUR PERIODE 2017 – 2019 - Alfansyah Surya Pratama; Ulil Hartono (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to determine the effect of Financial Distress. The independent variables in this research are Liquidity and Profitability, while the dependent variable is Financial Distress in manufacturing industry companies in the Indonesia Stock Exchange for the 2017-2019 period. The purposive sampling method was used as a sampling method, to obtain a sample of 15 companies. The data analysis technique is multiple linear regression that was carried out by processing the data using SPSS version 20. The results of the research found that Liquidity and Profitability did not have a significant effect on the Financial Distress of the manufacturing industry companies in the Indonesia Stock Exchange 2017-2019 period. Keywords: Liquidity; Profitability; Financial Distress